2017
DOI: 10.1155/2017/2956749
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted versus Open Hepatectomy for Live Liver Donor: Systematic Review and Meta-Analysis

Abstract: Objective To assess the feasibility, safety, and potential benefits of laparoscopy-assisted living donor hepatectomy (LADH) in comparison with open living donor hepatectomy (ODH) for liver transplantation. Background LADH is becoming increasingly common for living donor liver transplant around the world. We aim to determine the efficacy of LADH and compare it with ODH. Methods A systematic search on PubMed, Embase, Cochrane Library, and Web of Science was conducted in May 2017. Results Nine studies were suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Donor and recipient outcomes of hybrid and mini-laparotomy approaches are summarized in Tables 1 and 2 , respectively. Although inconsistently reported in case series, the benefits of reduced blood loss, wound pain and overall morbidity have been concluded in a meta-analysis comparing RW donor hepatectomy and open donor hepatectomy[ 57 ]. Types of complications were not specified.…”
Section: Present Statusmentioning
confidence: 99%
“…Donor and recipient outcomes of hybrid and mini-laparotomy approaches are summarized in Tables 1 and 2 , respectively. Although inconsistently reported in case series, the benefits of reduced blood loss, wound pain and overall morbidity have been concluded in a meta-analysis comparing RW donor hepatectomy and open donor hepatectomy[ 57 ]. Types of complications were not specified.…”
Section: Present Statusmentioning
confidence: 99%
“…Hand-assisted or hybrid donor hepatectomy has the same principles as pure laparoscopic donor hepatectomy, but the hepatic hilum is dissected and the liver is transected through a small open upper midline or transverse incision [34,68] . Similarly, the muscle layer is not interrupted, and, as a result, patients feel less abdominal wall pain than with the open hepatectomy [69] . However, the small incision of these techniques has drawbacks for obese patients with deep body cavities, such as longer operative duration, postoperative complications, and longer hospital stay, as it is difficult for surgeons to manage vascular injuries in these deeper areas [68,70,71] .…”
Section: Hand-assisted and Hybrid Donor Hepatectomymentioning
confidence: 99%
“…The vast majority of donor right hepatectomies has been performed through a right subcostal incision , but such incisions have been associated with a high incidence of scar tightness, sensation issues, and wound complications . In LADH, mobilization of the right liver is performed under laparoscopic guidance, and hepatic hilar dissection and parenchymal transection can be performed through an upper midline or transverse incision with instruments and techniques similar to those used in open donor hepatectomy .…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 99%
“…This approach does not interrupt the muscle layer and is associated with a lower incidence of abdominal wall discomfort than the open procedure . A recent meta‐analysis found that LADH had advantages over traditional open donor hepatectomy in terms of faster recovery, better cosmetic satisfaction, and less blood loss . Suh et al .…”
Section: Laparoscopy‐assisted Donor Hepatectomymentioning
confidence: 99%